Potential strains of thermophilic and organic solvent tolerant bacteria for lipase production using basal medium of palm kernel cake - Zubairi, Hidayah; Alam, Md. Zahangir; Salleh, Md. Noor; Mohd. Salleh, Hamzah (Universiti Sains Malaysia, 2017)
Palm Kernel Cake (PKC) consists many nutrients that are useful to be applied in the industry and directed studies towards utilization of this substrate in order to produce enzymes like lipases. This enzyme can be applied in various type of industry including pharmaceutical industries, food industries, cosmetics industries and others. Using palm kernel cake (PKC) as source of thermophilic bacteria, 53 bacterial strains were found survived at temperature 650C. However, after restreak several times, only 17 strains were found as pure thermophilic strains. Preliminary screening both qualitative and quantitative was performed to all 17 potential thermophilic bacterial strains and showed that only 11 purified thermophilic strains are lipase producer. Strain PKC-P1 produced highest enzyme activity (11.13 U/g). Thermostable lipase purified from thermophilic bacteria strain was stable at temperature 650C and pH 8.